Possibilities of Modelling Professional Training in Lithuania - Masaitytė, Ramunė; Brunevičiūtė, Raimonda (Acta Paedagogica Vilnensia, 2001)
The modernisation of vocational education and training system (VET) in Lithuania raises the problem of education and training model that could help the young generation solve their problems of socialisation and self-realisation. In this paper the main tendencies of vocational and training in the Middle and Eastern Europe as well as their influence to the vocational education and training model are analysed. The aim of the article is to distinguish the main tendencies in reforming VET in Europe in order to optimise this process in Lithuania. The article consists of three parts. The first part deals with the main European tendencies in vocational training; the second one is related to the review of the perspectives of modelling of VET in Lithuania. The third part is devoted to the discussion on the possibilities of the development of VET in Lithuania. Having analysed the tendencies of VET in Middle and Eastern Europe the model of universal vocational education and training is represented in order to delineate the perspectives of modernisation of vocational education in Lithuania with respect to the tendencies prevailing in Europe.